The Influence of Personality and Entrepreneurship Education on Interest in Entrepreneurship Faculty of Economics and Business Students with Attitude of Entrepreneurship as Intervening Variable - Andika Isma; Muhammad Rakib; Muhammad Satrio Mubaraq; Melati Suci (Department of Business and Entrepreneurship, Faculty of Economics and Business, Universitas Negeri Makassar, 2023)
Indonesia is a country that has a very large population and has abundant sources of wealth. The more developed a country, the more experts needed. There will be competition for jobs which causes an imbalance between the small number of jobs and the increasing number of job applicants. In addition, this can also increase the number of unemployed in a country. The most appropriate solution to reduce the number of unemployed is by entrepreneurship. Someone can open jobs to overcome the problem of unemployment that occurs due to the limited number of jobs provided by the government. This study aims to determine the direct and indirect effects of the influence of personality, entrepreneurship education on interest in entrepreneurship, with entrepreneurial attitudes. This study uses a quantitative approach with a descriptive explanatory type which describes the relationship between variables with a population of 153 students. The sampling technique used Proportional Random Sampling totaling 62 students of the Faculty of Economics and Business, Makassar State University. The results of the study show that directly and indirectly the influence of personality, entrepreneurship education with entrepreneurial attitudes has a significant effect on the interest in entrepreneurship. Based on the results of the research that has been done, this research can be a source of information or reference for teaching staff or lecturers in order to improve the quality of entrepreneurship education received by students and personality plays a role in improving the mindset in entrepreneurship skills.